(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Vitiligo is one of the most common skin diseases and is diagnosed by a chronic relapsing course with increasing severity, having a long chronic course that continues through life. The proportion of psychogenic ally-provoked exacerbations of vitiligo developing during life was determined by studying a representative sample of sick.